Agriculture and rural life in the Americas in the 21st Century - Brathwaite, Chelston W.D. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2019)
Cover four main topics: 1) I shall start with the topic of food security in the twenty-first century and the state of rural poverty; 2) I shall then discuss a new concept of agriculture and introduce the subject of its true contribution to development; 3) Then, I shall turn to the subject of agriculture, trade, the Inter-American agenda and the challenge of the modernization of agriculture; 4) I shall comment on the role of IICA in this context